The sociology student writer's manual - .; Rettig, Richard P.; Scott, Gregory M.; Johnson, William A. (Upper Saddle River, NJ : Prentice Hall, 1999)
This book is divided into five parts: A Handbook of style for sociology; How to conduct research in sociology; Thinking critically and arguing persuasively; Critical thinking exercises for introductory courses; and Sociology papers for advanced courses.
Keywords: Sociology; Report writing; Authorship; Report writing -- Handbooks, manuals, etc; Sociology -- Authorship -- Handbooks, manuals, etc; Sociology -- Research -- Handbooks, manuals, etc